Evaluation of Cross Match to Transfusion Ratio as a Tool of Quality Working In Tertiary Care Transfusion Services - Rabiah Asghar, Ayesha Junaid (Journal of Islamic International Medical College)
Objective: To evaluate the cross match to transfusion (CT) ratio, transfusion probability (%TP), and transfusion index (Ti) of packed red cells as a tool of quality working in the blood bank. Study Design: Descriptive observational study. Place and Duration of Study: This study was carried out from all indoor patient departments and blood bank over a 06 month period, from April 2024 to October 2024 at Shifa International Hospital. Materials and Methods: After receiving Institutional Review Board approval, the sample size was calculated using the WHO Calculator 2.0, data was collected through blood bank (HMIS) and department wise CT ratio, TP% and TI were calculated, entered and analysed using SPSS version 26. Results: 527 packed red cell products (RCC) were prepared after cross-matching, 198 (38%) were transfused, leaving 329(62%) unused with an overall cross CT of 2.6. These results showed that overall CT of blood bank was very close to target CT ratio . Departmental variations were observed, with surgery having a CT ratio of 2.1 indicating significant blood usage while Gynecology/Obstetrics and Liver transplant having 6.6, indicating overrequesting of blood products. Conclusion:The study found that blood usage is generally acceptable, with a CT ratio of 2.6. However, significant variation was seen across departments: the surgical department had an efficient CT ratio of 2.1, while Gynecology/Obstetrics and Liver Transplant showed higher ratios (6.6), pointing to possible over-ordering and wastage. The results emphasize the need for targeted approaches, including department-specific protocols and regular audits, to optimize blood utilization.